(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2022)
In the article, scientific and practical conclusions on the transition to International Financial Reporting Standards (IFRS) and its implementation are an urgent issue for all countries, as a result of the compilation of financial statements in many countries of the world, the creation of financial statements based on IFRS, and the transition to International Financial Reporting Standards in our